Optical coherence tomography-guided laser osteotomy: toward improvement of ablation efficiency - Hamidi Arsham; Cattin Philippe C.; Canbaz Ferda (Current Directions in Biomedical Engineering)
This study proposes an additional feature of optical coherence tomography (OCT) as a guidance system for laser surgery, aiming to enhance ablation efficiency during laser osteotomy. A long-range Bessel-like beam OCT system is integrated with an Er:YAG laser. The signal sensitivity of the OCT system is measured under various conditions encountered during laser osteotomy. The results demonstrate that the OCT sensitivity decreases from 87.53 dB to 79.54 dB and 68.93 dB in the presence of debris and water, respectively. These findings highlight the potential application signal sensitivity of OCT as a criterion for detecting the accumulation of water and debris, which could lead to a reduction in ablation efficiency during laser osteotomy using Er:YAG laser.